KEPEMIMPINAN SERVANT LEADERSHIP DAN MOTIVASI ORANG MUDA DALAM MENINGKATKAN PENDAMPINGAN ANAK TUNAGRAHITA DI KOMUNITAS ALMA PUTERI MALANG - Mingkol, Maria; Hatmoko, Tomas Lastari (Jurnal Pelayanan Pastoral, 2022)
The subject of this research is the young people who have completed their education at SMAK Bhakti Luhur and SMK Bhakti Luhur Malang who have dedicated themselves for 3 years to accompany mentally retarded children in the ALMA Puteri Malang community. In order to better assist the children, young people need to understand their role as a leader who serves and has motivation in carrying out activities according to the child's abilities. The problem of technological development affects young people in carrying out child assistance activities. Young people who are supposed to be the center of the organizers of activities to improve child assistance, are not able to complete work contracts. Therefore, researchers conducted a study to determine the servant leadership and the motivation of young people in increasing mentoring for mentally retarded children. In this research, the researcher uses the qualitative research method to examine the condition of natural objects. The data collection technique is triangulation (combined): interviews, observations and documentation so that the data obtained are in accordance with the objectives of the study. The results of the study show that servant leadership and the motivation of young people in increasing mentoring for mentally retarded children will be more developed if the leadership model itself prioritizes deep personal relationships, not merely functional or assisting and leading simply because of the task. The young people carry out activities according to the schedule and guidelines in the community, actively and creatively in providing activities to children so that children are happy and can participate in activities. Supporting factors are the availability of infrastructure, experts, clear guidelines, good cooperation and communication and the involvement of all community residents. While the inhibiting factor, it relates to the confdition of the children, likes sick, or lazy.